2014
DOI: 10.1007/s10661-014-3672-2
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of evaporative emissions from gasoline vehicles to the volatile organic compound inventory in Mexico City

Abstract: The strategy for decreasing volatile organic compound emissions in Mexico has been focused much more on tailpipe emissions than on evaporative emissions, so there is very little information on the contribution of evaporative emissions to the total volatile organic compound inventory. We examined the magnitudes of exhaust and evaporative volatile organic compound emissions, and the species emitted, in a representative fleet of light-duty gasoline vehicles in the Metropolitan Area of Mexico City. The US "FTP-75"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A German study found no measurable increases in atmospheric hydrocarbon concentrations in a Sealed Housing for Emissions Determination (SHED) in which an ORVRequipped vehicle was placed during refueling, although increases were detected at the beginning and end of refueling (9). Even though a study of presumably non-ORVR equipped vehicles in Mexico found older vehicles to have more evaporative emissions than newer ones (10), to the best of our knowledge, no assessment of the continuous functioning of ORVR systems to reduce emissions during vehicle refueling over the course of a vehicle's lifetime, within the conditions of an actual vehicle fleet, has been completed. It is possible that as vehicles age, hoses, seals, and other parts of the gas tank and ORVR system degrade, resulting in increased vapor emissions during refueling.…”
Section: Introductionmentioning
confidence: 99%
“…A German study found no measurable increases in atmospheric hydrocarbon concentrations in a Sealed Housing for Emissions Determination (SHED) in which an ORVRequipped vehicle was placed during refueling, although increases were detected at the beginning and end of refueling (9). Even though a study of presumably non-ORVR equipped vehicles in Mexico found older vehicles to have more evaporative emissions than newer ones (10), to the best of our knowledge, no assessment of the continuous functioning of ORVR systems to reduce emissions during vehicle refueling over the course of a vehicle's lifetime, within the conditions of an actual vehicle fleet, has been completed. It is possible that as vehicles age, hoses, seals, and other parts of the gas tank and ORVR system degrade, resulting in increased vapor emissions during refueling.…”
Section: Introductionmentioning
confidence: 99%
“…Martini et al evaluated the evaporative emissions from an Italian fleet of Euro 5 and earlier passenger cars using real-world mobility data and found that fleet averaged evaporative emissions for small passenger cars could be as high as 1.15 kg/vehicle/year [16]. Schifter et al examined VOC emissions in a representative fleet of light-duty gasoline vehicles in the Metropolitan Area of Mexico City and found that evaporative emissions from light-duty vehicles in the Metropolitan Area of Mexico City were estimated to be 39% of the total annual amount of hydrocarbons emitted [17]. Hata et al and Dong et al also evaluated the total annual evaporative emissions and OFP in Japan, Guangzhou, and Chicago by the model method [18][19][20].…”
Section: Introductionmentioning
confidence: 99%